2017
DOI: 10.2967/jnumed.117.193706
|View full text |Cite
|
Sign up to set email alerts
|

Dose Mapping After Endoradiotherapy with 177Lu-DOTATATE/DOTATOC by a Single Measurement After 4 Days

Abstract: Dosimetry of organs and tumors helps to assess risks and benefit of treatment with Lu-DOTATATE/DOTATOC. However, it is often not performed in clinical routine because of additional efforts, the complexity of data collection and analysis, and the additional burden for the patients. Aiming at a simplification of dosimetry, we analyzed the accuracy of a theoretically substantiated approximation, which allows the calculation of absorbed doses from a single measurement of the abdominal activity distribution. Activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
176
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 150 publications
(195 citation statements)
references
References 27 publications
13
176
1
5
Order By: Relevance
“…Activity kinetics in the kidneys was generally biexponential, with a negative short-lived component indicating further accumulation early after the activity administration, and a dominant long-lived component. The effective half-life of the dominant component was 37 6 12 h with 1 outlier at 97 h, which is slightly shorter than typically observed in octreotide endoradiotherapy (19)(20)(21). The renal absorbed dose per unit administered activity was 1.6 6 0.7 Gy/GBq 177 Lu-pentixather without nephroprotection, which is slightly higher than in octreotide endoradiotherapy (22).…”
Section: Dosimetry and Treatment Characteristicsmentioning
confidence: 77%
“…Activity kinetics in the kidneys was generally biexponential, with a negative short-lived component indicating further accumulation early after the activity administration, and a dominant long-lived component. The effective half-life of the dominant component was 37 6 12 h with 1 outlier at 97 h, which is slightly shorter than typically observed in octreotide endoradiotherapy (19)(20)(21). The renal absorbed dose per unit administered activity was 1.6 6 0.7 Gy/GBq 177 Lu-pentixather without nephroprotection, which is slightly higher than in octreotide endoradiotherapy (22).…”
Section: Dosimetry and Treatment Characteristicsmentioning
confidence: 77%
“…Madsen et al . and Hänscheid et al . both showed that single time point data can be used for estimating doses in lesions with population average data or late time point data sampling for 90 Y‐DOTATOC therapy and 177 Lu‐DOTATATE/DOTATOC therapy, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The simplest form of uptake value could be SUV; however, an SUV measured at a fixed time point may not be a good representative of time‐integrated activity in tumors because the normalization factor used for SUV calculation such as patient weight is hardly correlative with individual tumor's metabolism that governs the radiopharmaceutical uptake and absorbed dose. Although there is a single time point‐based technique called dose mapping, that method used a later time point (e.g., single measurement after 4 days for 177 Lu‐DOTATATE/DOTATOC) . For pretherapy dosimetry, which is performed within a small window of time before full therapeutic dose administration, a later time point requirement may be less desirable.…”
Section: Methodsmentioning
confidence: 99%
“…When using a priori information from a physiologically based pharmacokinetic model combined with Bayesian information about physiologically based pharmacokinetic model parameter distribution, the administered activity could be determined with acceptable accuracy using only 2 time points (4 h and 2 d) and thus allow a considerable reduction of needed data for individual dosimetry. Hänscheid et al (41) suggested that a single quantitative 3-dimensional image might be sufficient to provide values for absorbed doses for PRRT with an accuracy of 10%-15%. However, the results of both studies need to be confirmed in larger patient cohorts.…”
Section: Determining Optimal Time Pointsmentioning
confidence: 99%